Positive Exercise Experience Facilitates Behavior Change via Self-Efficacy. (August 2014) - Parschau, Linda; Fleig, Lena; Warner, Lisa Marie; Pomp, Sarah; Barz, Milena; Knoll, Nina; Schwarzer, Ralf; Lippke, Sonia
Purpose. Motivational processes can be set in motion when positive consequences of physical exercise are experienced. However, relationships between positive exercise experience and determinants of the motivational and the volitional phases of exercise change have attracted only sparse attention in research. Method . This research examines direct and indirect associations between positive experience and motivational as well as volitional self-efficacy, intention, action planning, and exercise in two distinct longitudinal samples. The first one originates from an online observational study in the general population with three measurement points in time ( N = 350) and the second one from a clinical intervention study in a rehabilitation context with four measurement points ( N = 275). Results . Structural equation modeling revealed the following: Positive experience is directly related with motivational self-efficacy as well as intentions in both samples. In the online sample only, positive experience is associated with volitional self-efficacy. In each sample, experience is indirectly associated with action planning via motivational self-efficacy and intentions. Moreover, action planning, in turn, predicts changes in physical exercise levels. Conclusions . Findings suggest a more prominent role of positive experience in the motivational than in the volitional phase of physical exercise change. Thus, this research contributes to the understanding of how positive experience is involved in the behavior change process.